3D acquisition, modelling and visualization of North German castles by digital architectural photogrammetry - Thomas Kersten and Carlos Acevedo Pardo and Maren Lindstaedt (The international archives of photogrammetry, remote sensing and spatial information sciences, 2004)
In order to create virtual realities, three-dimensional scenes must be generated digitally. Frequently such scenes are freely invented in computer games and have little or nothing to do with reality. The Department of Geomatics of the Hamburg University of Applied Sciences (HAW Hamburg) records historical buildings and castles for detailed virtual reality applications, which can be used in visualizations, simulation and planning for tourism, navigation, facility management, architecture, cultural heritage and city planning. A condition of such modelling and visualization is a complete 3D acquisition of the objects, e.g. with geodetic measuring techniques, terrestrial laser scanners or with digital architectural photogrammetry. Three north German castles in Celle (Lower Saxony), Ahrensburg and Glücksburg (both in Schleswig-Holstein) were recorded photogrammetrically using a digital SLR Camera (Fujifilm FinePix S1 Pro) and later modelled and visualized. The data processing steps from data recording, determination of photo orientation, camera calibration and CAD modelling to visualization are described in the paper. The results of the photogrammetric 3D data acquisition and CAD object reconstruction are summarized and the visualization of the virtual castles is presented. Some economic aspects of the project work are finally discussed.
Keywords: Architecture; CAD; Cultural heritage; Digital; Modelling; Photogrammetry; Virtual reality; Visualization